The optimal dose of Ramelteon for the better treatment adherence of delayed sleep–wake phase disorder: a dropout rate study - Takagi, Shunsuke; Sugihara, Genichi; Takahashi, Hidehiko; Inoue, Yuichi (Frontiers in Neurology, 2023)
Background: Evidence regarding the effectiveness of melatonin receptor agonists in treating delayed sleep-wake phase disorder (DSWPD) remains limited. This study aimed to determine the optimal dose of ramelteon, a melatonin receptor agonist, for the better treatment adherence of DSWPD.Methods: The patients who were diagnosed definitely as having DSWPD by board-certified physicians specialized in sleep medicine and started to receive strategically timed ramelteon medications after the diagnosis were included. Data on the initial ramelteon dose and follow-up duration (up to 24 months) were collected retrospectively. Patients with treatment discontinuation, changes in ramelteon dose, or the addition of other sleep-related medications were considered dropouts. Kaplan-Meier estimates, log-rank tests, and Cox regression analyses were performed.Results: Overall, 373 patients were analyzed. The findings revealed that the 2 mg dose of ramelteon was associated with a lower dropout rate compared to the other doses (8 mg, 4 mg, and 1 mg). The dropout rate for the 2 mg group was estimated to have a hazard ratio (HR) of 0.5762 when compared with the 8 mg dose group. Sex did not reveal a significant HR, whereas older age exhibited a small but significant HR (0.9858).Conclusion: For achieving better adherence, a dosing regimen of strategically timed 2 mg ramelteon may be the best for the treatment of DSWPD. The therapeutic dose window for better adherence seems to center around 2 mg of ramelteon. Furthermore, caution should be exercised when treating younger patients to prevent dropouts.